Considerations for physicians using ketamine for sedation of children in emergency departments - Kim, Woo Sung; Ku, Ji Yeon; Choi, Hanbyul; Choi, Hyo Jeong; Kim, Ho Jung; Lee, Bora (Clinical and experimental emergency medicine, 2017)
Ketamine use in emergency departments (EDs) for procedural sedation and analgesia is becoming increasingly common. However, few studies have examined patient factors related to adverse events associated with ketamine. This study investigated factors for consideration when using ketamine to sedate pediatric ED patients. The study included pediatric patients receiving ketamine for laceration repair in the ED. Before sedation, information was collected about upper respiratory tract infection symptoms, allergy history, and fasting time. Patients received 2 mg/kg ketamine intravenously or 4 mg/kg ketamine intramuscularly. The primary outcomes were adverse events due to ketamine. We studied 116 patients aged 8 months to 7 years (2.8±1.5 years). The group with adverse events was significantly younger on average than the group without adverse events (2.5±1.5 vs. 3.1±1.5, P=0.028). Upper respiratory tract infection symptoms were not significant variables affecting ketamine sedation (48.9% vs. 43.7%, P=0.719). There was no significant association between duration of fasting and adverse events (P=0.073 and P=0.897, respectively), or between food type and adverse events (P=0.734). However, the number of attempts to sedate and ketamine dose correlated with adverse events (P<0.001 and P=0.022, respectively). In multiple logistic regression analysis, intravenous injection and ketamine dose were significant factors (odds ratio, 16.77; 95% confidence interval, 1.78 to 498.54; odds ratio, 4.37; 95% confidence interval, 1.59 to 22.9, respectively). Emergency medicine physicians should consider injection type and ketamine dose when using ketamine sedation while suturing lacerations.